Non-Chemical Treatments for the Pre- and Post-Harvest Elicitation of Defense Mechanisms in the Fungi–Avocado Pathosystem - Juan Antonio Herrera-González (MDPI AG, 2021)
The greatest challenge for the avocado (Persea americana Miller) industry is to maintain the quality of the fruit to meet consumer requirements. Anthracnose is considered the most important disease in this industry, and it is caused by different species of the genus Colletotrichum, although other pathogens can be equally important. The defense mechanisms that fruit naturally uses can be triggered in response to the attack of pathogenic microorganisms and also by the application of exogenous elicitors in the form of GRAS compounds. The elicitors are recognized by receptors called PRRs, which are proteins located on the avocado fruit cell surface that have high affinity and specificity for PAMPs, MAMPs, and DAMPs. The activation of defense-signaling pathways depends on ethylene, salicylic, and jasmonic acids, and it occurs hours or days after PTI activation. These defense mechanisms aim to drive the pathogen to death. The application of essential oils, antagonists, volatile compounds, chitosan and silicon has been documented in vitro and on avocado fruit, showing some of them to have elicitor and fungicidal effects that are reflected in the postharvest quality of the fruit and a lower incidence of diseases. The main focus of these studies has been on anthracnose diseases. This review presents the most relevant advances in the use of natural compounds with antifungal and elicitor effects in plant tissues.